Assessment of ovarian follicular reserve according to ultrasound data based on machine learning methods - Fedor A. Laputin; Ivan V. Sidorov; Andrey S. Moshkin (Digital Diagnostics, 2024)
BACKGROUND: Ovarian reserve reflects a woman's ability to successfully realize reproductive function. The assessment of ovarian reserve is an urgent task for clinical practice [1] and is important in scientific research. The use of computerized diagnostic image processing methods can accelerate and facilitate the performance of routine tasks in clinical practice. Their use in retrospective data analysis for scientific purposes allows to increase the objectivity of the study and supplement it with auxiliary information [2].